Identification of Two Types of Metallogenic Fluids in the Ultra-Large Huize Pb–Zn Deposit, SW China. (27th August 2017) - Zhang, Yan; Han, Runsheng; Wei, Pingtang; Wang, Lei
Abstract : This work investigates the ultra-large Huize Pb–Zn deposit, based on the results of preceding studies and detailed field geological surveys. The existing findings were reorganized and reinterpreted and supplemented with C–H–O isotopic measurements, which resulted in the identification of two different metallogenic fluids: a high temperature, low salinity, and acidic Fluid A, which originates from deep-seated fluids and is enriched in lighter C and O isotopes (−3‰ < δ 13 C‰ < −4‰ ; 10‰ < δ 18 O‰ < 17‰ ; −92‰ < δ D‰ < −50‰ ), and a low temperature, high salinity Fluid B, which is a subsurface brine formed by atmospheric precipitation. Fluid B is characterized by heavier C–O–H isotopic compositions (−2‰ < δ 13 C‰ < 1‰ ; 2‰ < δ 18 O‰ < 24‰ ; −66‰ < δ D‰ < −43‰ ) than Fluid A and cycles continuously within the strata. We hypothesize that the Huize Pb–Zn deposit is the result of large-scale fluid migration from deep regions of the crust. These upward-moving fluids extracted metallic elements from carbonate strata of various ages, forming a metal-rich metallogenic fluid (Fluid A). After higher-grade ores were precipitated from the fluid following decompression boiling, it then mixed with Fluid B and continued to precipitate sulfides.